Preventive Strategies for Major Complications in Maintenance Hemodialysis - Windu Unggun Cahya Jalu Putra; Raden Bagus Edy Santoso; Wirda Wirda; Jumain main; Niswa Salamung (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Patients undergoing maintenance hemodialysis are at high risk of complications, including intradialytic hypotension, vascular access infection, anemia instability, and cardiovascular events. These complications significantly contribute to morbidity, hospitalization, and mortality. Preventive and structured management strategies are essential to improve clinical outcomes. This study aimed to identify and evaluate evidence on preventive interventions for major complications in maintenance hemodialysis patients. This systematic review was conducted following the PRISMA 2020 guidelines. A comprehensive literature search was performed in PubMed, Scopus, and Google Scholar for studies published between 2023 and 2025. Eligible studies included randomized controlled trials and observational studies involving adult maintenance hemodialysis patients and evaluating preventive interventions targeting major dialysis-related complications. Study selection, data extraction, and quality assessment were conducted independently by two reviewers using predefined eligibility criteria. Ethical approval was not required because the review analyzed data from previously published studies. After screening 1,086 records and assessing 81 full-text articles, 12 studies met the inclusion criteria and were included in the qualitative synthesis. The included studies demonstrated that protocol-based and preventive interventions significantly reduced complication rates. Individualized ultrafiltration adjustment, cool dialysate application, and biofeedback systems reduced intradialytic hypotension. Vascular access care bundles lowered infection rates. Algorithm-based anemia management improved hemoglobin stability, while structured fluid management and cardiovascular screening reduced hospitalization and adverse cardiovascular events. Structured, nursing-driven, and preventive management strategies represent effective approaches to reducing major complications in maintenance hemodialysis patients. The integration of standardized monitoring protocols, evidence-based preventive interventions, and multidisciplinary care models should be prioritized in clinical practice to enhance patient safety, reduce hospitalization, and improve long-term patient outcomes.Keywords: hemodialysis; complications; intradialytic hypotension; anemia; infection prevention